Advances in mechanical and electronic engineering : Volume 2 - Lin, Sally; Jin, David (Lecture Notes in Electrical Engineering, 2012)
This book includes the volume 2 of the proceedings of the 2012 International Conference on Mechanical and Electronic Engineering(ICMEE2012), held at June 23-24,2012 in Hefei, China. The conference provided a rare opportunity to bring together worldwide researchers who are working in the fields. This volume 2 is focusing on Mechatronic Engineering and Technology,  Electronic Engineering and Electronic Information Technology .